PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PENGELOLAHAN KELAS GUNA MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII DI SMP PGRI 08 MALANG - Tantra Jaya Putra Tulungagung; Muhammad Hanif; Moh. Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Based on information in the field, some educators ignore small things that can increase students' motivation and enthusiasm for learning. The existence of Islamic religious education teachers is expected to be able to overcome student problems in learning, learning motivation also plays a major role in shaping the character of students. The purpose of this study was to describe the role of Islamic religious education teachers in PGRI 08 Malang junior high school. This research uses descriptive qualitative methods and case studies. The data analysis used is interactive data analysis. The form of classroom management in increasing students' learning motivation at PGRI 08 Junior High School Malang, among others, is providing continuous direction, providing material reinforcement after each lesson, and all things that aim to increase student learning motivation in PGRI 08 Junior High School. Poor. The supporting factors in managing the class include the facilities and infrastructure used, while the inhibiting factors in managing a class include inadequate learning media, and the lack of awareness of students in learning. From this background, the researchers have a research emphasis, as follows: The role of Islamic Religious Education Teachers in Classroom Management to Improve Student Motivation for Class VIII In Junior High School PGRI 08 Malang and what are the supporting and inhibiting factors in classroom management that teachers do to improve motivation to learn in the subject of Islamic religious education in junior high school PGRI 08 Malang.